Absence of human papillomavirus in nasopharyngeal swabs from infants in a population at high risk of human papillomavirus infection. Issue 2 (18th June 2021) - Smith‐Vaughan, Heidi C; Cheng, Allen C; Tabrizi, Sepehr N.; Wurzel, Danielle F; Beissbarth, Jemima; Leach, Amanda J; Morris, Peter S; Binks, Michael J; Torzillo, Paul J; Chang, Anne B; Marsh, Robyn L
ABSTRACT: Maternal urogenital human papillomavirus (HPV) infection may place neonates at risk of HPV acquisition and subsequently lower respiratory infections as HPV can influence development of immunity. The respiratory HPV prevalence is not known in remote‐dwelling Aboriginal infants, who are at high risk of respiratory infection and where the population prevalence of urogenital HPV in women is high. These data are necessary to inform HPV vaccination regimens. A retrospective analysis using PCR specific for HPV was performed on 64 stored nasopharyngeal swabs from remote‐dwelling Aboriginal infants < 6 months of age, with and without hospitalised pneumonia. HPV DNA was not detected in any specimen. Despite the negative result, we cannot exclude a role for HPV in respiratory infections affecting infants in this population; however, our data do not support HPV as an important contributor to acute respiratory infection in remote‐dwelling Aboriginal children. Abstract : In populations at high risk of urogenital HPV infection, newborns are at risk of acquiring HPV which may lead to impaired immunity and increased risk of chest infection. In our study, infant nose swabs were HPV negative suggesting that HPV isn't a common child health issue in this population.